Theoretical Insights into the Nature of Oxidant and Mechanism in the Regioselective Syn‐dihydroxylation of an Alkene with a Rieske oxygenase inspired Iron Catalyst. Issue 17 (10th July 2018) - Roy, Lisa
Abstract: Selective C=C bond oxidation is a fundamental process in Nature and has potential utility in organic synthesis. Herein, ab initi o and density functional techniques are employed to investigate the nature of the oxidant and mechanism in alkene oxidation by two H2 O2 activating Rieske oxygenase inspired iron catalysts, one of which is more sterically encumbered. Electronic structure analysis reveals that the mechanism involves a water‐assisted homolytic O−O bond cleavage of the peroxide moiety to generate an Fe IV (O . )OH radical intermediate, followed by epoxidation or syn ‐dihydroxylation of the alkene substrate. Furthermore, it is shown that a greater degree of structural reorganization due to higher steric repulsion between the substrate and bulky substituents selectively avoids epoxidation in one of the complexes, thus directing it towards exclusive hydroxylation. Additionally, the rate‐determining barrier for cis ‐diol release is curtailed by ∼14 kcal/mol due to synergistic assistance from Lewis acid. Our study therefore highlights the crucial role of ligand modification and additives which can be further engineered to achieve enzyme‐like optimum activity. Abstract : Enzyme‐like optimum activity : Sterically encumbered Si i Pr3 substituents on the TPA ligand inhibits electron transfer from C=C bond to πyz * on Fe IV =O oxidant, which raises the reorganization energy and increases the barrier for epoxidation to direct exclusive regioselective cis ‐dihydroxylation.